(untitled) (Politeja, 2023)
The purpose of this article is to show how the EHL is used for the interpretation, awareness, and transmission of heritage and memory. As part of the EU European Heritage Label (EHL) program, Polish institutions received six distinctions in the years 2014-2019, which places Poland high in the ranking of the awarded Brands in Europe. Polish institutions are obligated to spreading knowledge about the cultural heritage of Europe. On the one hand, EHL’s task is to raise awareness and transmit common values, elements of European history, and heritage, which can be interpreted as promoting “uni memory.” On the other hand, EHL aims to deepen intercultural dialogue and synergy, recognizing the values of diversity, which can be understood as promoting the idea of plural memory. The EHL organizers in Poland are obliged (by the provisions of the EU Program) to conduct a European narrative, but in practice, they sometimes remain at the stage of restoring and refreshing the memory of the site, organizing local memory, and revising the regional policy due to “dormant memory” during the communist period.